Novel peptides that inhibit the propagation of Newcastle disease virus - Ramanujam, P.; Tan, W. S.; Nathan, S.; Yusoff, K. (Springer, 2002)
A disulfide constrained random heptapeptide library displayed on filamentous bacteriophage M13 was applied to select specific ligands that interact with Newcastle disease virus (NDV). A fusion phage carrying the amino acid sequence TLTTKLY was selected from the panning procedure. An antibody competition assay showed that the selected phage was capable of competing with the polyclonal antibodies raised against NDV for binding sites on the virus. Determination of the binding affinity of this phage with NDV by an equilibrium binding assay in solution revealed two different dissociation constants, suggesting that there could be two distinct binding sites for the phage on NDV. Synthetic peptides with the sequence CTLTTKLYC, either in linear or cyclic conformations inhibited the binding of phage bearing the same sequence to NDV. These peptides also inhibited the hemolytic activity of the virus as well as its propagation in embryonated chicken eggs.